Sources and Leakages of Microplastics in Cruise Ship Wastewater - Folbert, Maartje E. F.; Corbin, Christopher; Löhr, Ansje J. (Frontiers in Marine Science, 2022)
To date, the contribution of sea-based sources to the global marine litter and plastic pollution problem remains poorly understood. Cruise ships produce large amounts of wastewater and concentrate their activities in fragile and ecologically valuable areas. This paper explores for the first time the sources of microplastics in cruise ship wastewater, as well as their pathways from source to sea. It thereto uses a novel approach for the identification of sources and pathways, based on scientific literature on microplastic sources and pathways, literature on cruise operations and wastewater management as well as a questionnaire among cruise lines. The study highlights personal care and cosmetic products, cleaning and maintenance products and synthetic microfibers released from textiles in laundry as relevant source categories. Untreated grey water and the overboard discharge of biosludge, resulting from the treatment of sewage and grey water, were identified as key pathways. Cruise lines can reduce microplastic emissions by adapting their purchasing policies for personal care, cosmetic, cleaning and maintenance products and professional textiles. In addition, the holistic management of all wastewater streams and resulting waste products is essential to prevent leakages of microplastics from cruise ships to vulnerable coastal and marine ecosystems. Furthermore, the approach can be used to guide company-level assessments and can be modified to address microplastic leakages in other maritime sectors.